Freely Available, Online Videos To Support Neurological Physiotherapists and Students in Task-Specific Training Skill Acquisition: A Scoping Review - Towersey, Nicola; Sasse, Kelvin; Stavric, Verna; Alder, Gemma; Saywell, Nicola (BMC, 2024)
Background Videos to support learning of clinical skills are effective; however, little is known about the scope and educational quality of the content of freely available online videos demonstrating task-specific training (TST). This review aimed to determine the extent, characteristics of freely available online videos, and whether the content is suitable to guide skill acquisition of task-specific training for neurological physiotherapists and students. Methods A scoping review was conducted. Google video and YouTube were searched in December 2022. Videos that met our eligibility criteria and were explicitly designed for (TST) skill acquisition were included in the report. Results Ten videos met the inclusion criteria and were difficult to find amongst the range of videos available. Most were presented by physiotherapists or occupational therapists, originated from the USA, featured stroke as the condition of the person being treated, and involved a range of interventions (upper limb, constraint induced movement therapy, balance, bicycling). Most videos were created by universities or private practices and only two used people with a neurological condition as the participant. When the content of videos and their presentation (instruction and/or demonstration), was assessed against each key component of TST (practice structure, specificity, repetition, modification, progression, feedback), five of the videos were rated very suitable and five moderately suitable to guide skill acquisition. Most videos failed to demonstrate and provide instruction on each key component of TST and were missing at least one component, with feedback most frequently omitted. Conclusions There are many freely available online videos which could be described as demonstrating TST; very few are suitable to guide skill acquisition. The development of a standardised and validated assessment tool, that is easy to use and assesses the content of TST videos is required to support learners to critically evaluate the educational quality of video content. Guidelines based on sound teaching theory and practice are required to assist creators of online videos to provide suitable resources that meet the learning needs of neurological physiotherapists and students.
Keywords: 1117 Public Health and Health Services; 1302 Curriculum and Pedagogy; Medical Informatics; 3202 Clinical sciences; 3901 Curriculum and pedagogy; 3904 Specialist studies in education